The movement of developing the educational institutions during the Timurid period and the role of the sultans and Khavatin in its advancement. - فریدون الهیاری; ابوالحسن فیاض انوش; معصومه گودرزی (پژوهش‌های تاریخی ایران و اسلام, 2016)
Learning from ancient times to the present were over complex system in which the Proportional to the degree of civilization, governmental, political, social and religious change circumstances in any period.  One of these periods is the reign of Timur's successor’s era (912-807AH.). In this era gained momentum educational institution and the kings, princes, rulers, scholars Khavatin and each had their share in the growth of the institution concerned Following the death of Timur in the territory of his successor , Shahrukh, Despite the relative peace, political stability and security was to improve the of livelihoods. Then, the scientific and cultural movement was prepared, and the schools, libraries and learning circles was built underlying to the efforts of many kings Khavatin and Rulers. Timurid sultan, the one hand, providing educational facilities and for the welfare of teachers and students on the strides of science and the improvement and the other hand, pursued the legitimate government. The most striking feature of Timurid rule was penchant of some these sultans for the growth of science, literature and built the educational centers. The multitude construction of the educational institutions It was so, that Jami claimed, has not made the school size in any period of Iran history .In this study,  the authors were focused  on  library resources and used a  descriptive and analytical method .One of  the most important findings of this study was the  significant role of the  kings, ministers and  Khavatin on  the construction of schools and   the educational institutions, function of libraries , writing  the books and follow to a systemic educational system.